2015
DOI: 10.1128/jvi.02473-14
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Fitness of Influenza B Viruses with Neuraminidase Inhibitor-Resistant Substitutions in a Coinfection Model of the Human Airway Epithelium

Abstract: Influenza A and B viruses are human pathogens that are regarded to cause almost equally significant disease burdens. Neuraminidase (NA) inhibitors (NAIs) are the only class of drugs available to treat influenza A and B virus infections, so the development of NAI-resistant viruses with superior fitness is a public health concern. The fitness of NAI-resistant influenza B viruses has not been widely studied. Here we examined the replicative capacity and relative fitness in normal human bronchial epithelial (NHBE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 77 publications
(80 reference statements)
2
20
1
Order By: Relevance
“…We show that the MUT-Y273 virus had equivalent NA activity and expression to the WT-H273 virus, but delayed growth in cell culture. Previous experiments using a rg-H273Y virus showed that relative to the rg-WT, the rg-H273Y virus had significantly higher NA activity and surface expression, and superior replication kinetics in a competitive mixtures experiment in normal human bronchial epithelial cells (14, 22, 23). The discrepancy in these fitness outcomes between our 2015 H273Y virus and a 1998 rg-H273Y virus may be due to differences in viral background (16 amino acid differences).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We show that the MUT-Y273 virus had equivalent NA activity and expression to the WT-H273 virus, but delayed growth in cell culture. Previous experiments using a rg-H273Y virus showed that relative to the rg-WT, the rg-H273Y virus had significantly higher NA activity and surface expression, and superior replication kinetics in a competitive mixtures experiment in normal human bronchial epithelial cells (14, 22, 23). The discrepancy in these fitness outcomes between our 2015 H273Y virus and a 1998 rg-H273Y virus may be due to differences in viral background (16 amino acid differences).…”
Section: Discussionmentioning
confidence: 98%
“…A number of different NA substitutions at conserved amino acid positions (e.g. E117, D197, I221 and H273) have previously been described to confer reduced inhibition by the NAIs in vitro (8, 12-21), but the impact of these substitutions on enzyme function, virus replication or transmissibility, has only been assessed in a limited number of studies (14, 22, 23). The fitness of influenza B viruses with either the H273Y or D197N NA substitution is of particular interest as a number of viruses with either substitution have been recently found in patients in community settings who, unlike hospitalized or immunocompromised patients, do not typically receive NAI treatment (8, 9, 17, 18, 24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of antiviral therapies is another approach to increase our readiness for pandemic outbreaks. Antivirals such as oseltamivir, which target viral processes, have shown utility, but drug resistant viruses can emerge [4]. Antivirals that target host processes important for the virus have potential to circumvent the development of resistance, and targeting of host processes has shown therapeutic promise for other viruses [5].…”
Section: Introductionmentioning
confidence: 99%
“…Novel IBV antivirals are needed. There are only two approved antivirals (oseltamivir and zanamivir) for treatment of pediatric influenza virus infections (26,27). Additionally, as with IAV, antiviral resistance is present in IBV isolates (28)(29)(30).…”
mentioning
confidence: 99%